Monitoring the sustainable Development of the Electronic Industry - N. A. Kazakova; V. G. Kogdenko (Финансы: теория и практика)
The subject of the study is the Russian electronic industry as a strategically important sector that ensures national security and cybersecurity in all areas of activity. The relevance of the study is due to insufficient efficiency and consistency of the results of the existing monitoring of the development of the electronics industry, which is related to the lack of comprehensive information and analytical tools for diagnosis of indicators of sustainable development of industry. The purpose of the study is to develop a flexible situational approach to monitoring the electronics industry, taking into account the industry strategy to expand production of civilian products, as well as to justify the effectiveness of financing tools and increasing the sustainable development of the industry. As a result, a monitoring technique based on data from industry statistics, the Spark-Interfax information resource, and big data analytics for organizations in the electronics industry, with eventual industry aggregation, was developed. The sectoral structure was examined in accordance with the methodology, the market situation and business models were evaluated, and the risks and shortcomings of financing the sector were identified. The approach ensures monitoring of the transformation of the industry, creation of a fair competitive market, increase in the share of efficient private Russian companies and their integration into the global ecosystem. The scientific novelty of the study lies in the selection of sectoral assessment indicators, the use of information resources and big data technology, which provide regular diagnostics of the industry. The theoretical significance of the study is the development and adaptation of industry analysis to the specifics of the electronics industry, as well as the inclusion of sustainable development indicators. The results of the study are of practical significance for the professional Association of organizations of the radio-electronic industry of Russia, government regulators and private investors interested in operational information about the state and trends of the development of the industry and its financing tools.